(untitled) (Journal of actual problems of jurisprudence, 2026)
In the context of digital transformation in the country’s judicial system, the introduction of electronic formats in court proceedings, including the preparation of procedural documents, and the use of artificial intelligence are becoming a necessary stage in the development of justice. The e-justice system forms a complex structure, representing a set of independent and interacting elements that represent forms of application and use of information and communication technologies in civil proceedings, united by the goal of solving problems of civil litigation. The elements of the e-justice system are the forms of application and use of information and communication technologies in the consideration and resolution of cases by the courts in accordance with the goals and objectives of civil proceedings. Today’s rapid evolution in information systems has led to the complete computerization of virtually all spheres of society, including the legal sphere. One area where new technologies are effectively utilized and achieved through digitalization is the court system. Digital technology for the judicial sphere offers the opportunity to increase efficiency, ensure the transparency of judicial decisions, reduce the burden on the courts, eliminate bureaucratic relations, and ultimately reduce the level of corruption in the courts. Artificial intelligence systems allow individuals to search for judicial decisions and predict the possible outcome of court cases. The gradual development of the transition to digitalization of the judicial system is evidenced by the creation of e-courts and e-litigation as the main platforms for implementing e-justice. However, rapidly developing economic relations in the context of globalization have led to an increase in corporate disputes, both transnationally and within each independent state. Kazakhstan is no exception to this natural legal phenomenon. Therefore, it is necessary to study specific areas of the analytical and organizational-procedural activities of bailiffs, paying particular attention to mathematically correct machine learning of artificial intelligence. The authors propose addressing the issues analyzed in the study through the active participation and oversight of judges, tailoring recommendations to specific court conditions, and integrating artificial intelligence and blockchain technologies. To further develop the e-justice system, it is important to enhance the functionality of e-court platforms through the integration of artificial intelligence and blockchain technologies. Overall, this will contribute to further improving the accessibility and efficiency of judicial proceedings. Keywords: artificial intelligence, e-court system, corporate disputes, civil litigation, digital transformation.